Kontribusi Penerimaan Guru Pada Pelatihan Kurikulum Mardeka dan Kompetensi Pedagogik Terhadap Implementasi Kurikulum Mardeka di SMK Negeri 1 Painan - Deswina, Melri; Darwin, Widya; Jusmardi, Jusmardi; Fernandes, Erik; Rahmadani, Rahmadani (Universitas Lampung, 2023)
The purposed of the research is to reveal the contribution of teachers acceptence of mardeka curriculum training and pedagogic competence towards the implementation of mardeka curriculum at SMK Negeri 1 Painan. The hypothesis are: (1) there are contribution of teachers acceptence of curriculum mardeka; (2) there are contribution of pedagogic competence towards the implementation of mardeka curriculum; and (3) there are contribution of teachers acceptence of mardeka curriculum training and pedagogic competence towards the implementation of mardeka curriculum at SMK Negeri 1 Painan. The findings of the research were: (1) the teachers acceptance of mardeka curriculum were significanly contributed to the implementation of curriculum mardeka, (2) the contribution of pedagogic competence towards the implementation of curriculum mardeka were significanly contributed to curriculum implementation, and (3) the teachers acceptence to mardeka curriculum and the pedagogic compentence in conjuction with the contribution of the implementation of mardeka curriculum The conclusion is that the contribution of teachers acceptence of mardeka curriculum training and pedagogic competence SMK Negeri 1 Painan was the key factors that contributed towards the implementation of mardeka curriculum.Key Word: Kurikulum Mardeka, Penerimaan Guru, Pelatihan, Pedagogik